Laparoscopy-assisted distal gastrectomy with lymph node dissection for gastric cancer - Thanh, Phan Hai; Loc, Duong Xuan; Thanh, Dang Nhu; Phan, Hoang Ngoc; Phuong, Hoang Trong Nhat; Linh, Ho Van; Thien, Ho Huu; Vu, Pham Anh; Hà, Le Manh; Hiep, Pham Nhu; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.